Regulation of calcium homeostasis in endoplasmic reticulum–mitochondria crosstalk: implications for skeletal muscle atrophy - Xuexin Li; Xin Zhao; Zhengshan Qin; Jie Li; Bowen Sun; Li Liu (Cell Communication and Signaling)
Abstract This review comprehensively explores the critical role of calcium as an essential small-molecule biomessenger in skeletal muscle function. Calcium is vital for both regulating muscle excitation–contraction coupling and for the development, maintenance, and regeneration of muscle cells. The orchestrated release of calcium from the endoplasmic reticulum (ER) is mediated by receptors such as the ryanodine receptor (RYR) and inositol 1,4,5-trisphosphate receptor (IP3R), which is crucial for skeletal muscle contraction. The sarcoendoplasmic reticulum calcium ATPase (SERCA) pump plays a key role in recapturing calcium, enabling the muscle to return to a relaxed state. A pivotal aspect of calcium homeostasis involves the dynamic interaction between mitochondria and the ER. This interaction includes local calcium signaling facilitated by RYRs and a “quasi-synaptic” mechanism formed by the IP3R-Grp75-VDAC/MCU axis, allowing rapid calcium uptake by mitochondria with minimal interference at the cytoplasmic level. Disruption of calcium transport can lead to mitochondrial calcium overload, triggering the opening of the mitochondrial permeability transition pore and subsequent release of reactive oxygen species and cytochrome C, ultimately resulting in muscle damage and atrophy. This review explores the complex relationship between the ER and mitochondria and how these organelles regulate calcium levels in skeletal muscle, aiming to provide valuable perspectives for future research on the pathogenesis of muscle diseases and the development of prevention strategies.